A prevention approach to undocumented forms of migration across the Mediterranean Sea: a critical assessment from Italy [version 1; peer review: 2 approved] - Ombretta Ingrascì; Monica Massari; Simona Miceli (Open Research Europe, 2024)
This article is aimed at providing a solid empirical basis which can inspire the development of more informed strategies in the field of prevention of undocumented forms of migration across the Mediterranean. Besides, more traditional forms of human smuggling and trafficking, a new phenomenon has emerged especially along the Central Mediterranean route, i.e. trafficking in itinere, which affects people who had originally sought irregular travel services but then ended up in being kidnapped, tortured and kept in detention centres during their migratory path. Therefore, their irregular journey to Europe becomes the only way to survive. The methodology adopted draws from in-depth interviews with experts in Italy – especially prosecutors, law enforcements officers, representatives of NGOs and journalists -, the analysis of institutional reports and sources, as well as biographical accounts provided by migrants. The analysis critically addresses the countereffects produced by the hardening of borders and militarisation of sea routes in the Mediterranean area especially in terms of enhancement of the smuggling industry, increased human rights violations and clandestinization of migrants whose experiences and knowledge are too often underrepresented or misrepresented in the public debate. This results in a negative impact on migration policy-making and on the adoption of more effective measures aimed at addressing the governance of borders and the reception system in the EU. In conclusion, some recommendations are made, which call for a reconsideration of the distinction between economic and political migrants, an enhancement of the right to migrate which can guarantee safer forms of mobility toward the EU, a serious reconsideration of the politics of externalization of European borders with its extremely severe costs in terms of human rights, and a stronger valorisation of migrants’ actual needs, expectations and projects in the design of more effective policies aimed at improving the overall EU reception system.